The Living Values Education (LVE) Approach Based on Religious Moderation at Sekolah Madania Bogor - Taufik Hidayatulloh; Theguh Saumantri; Clare Harvey (Edukasia Islamika : Jurnal Pendidikan Islam, 2023)
Character education has become increasingly crucial in facing the complexity of challenges in the 21st century. Education serves as one of the fundamental pillars in shaping individual character and personality. Amidst the growing religious and cultural pluralism, values-based education becomes more relevant in cultivating a generation with global awareness and inclusive attitudes. The purpose of this research is to delve into the implementation of Living Values Education (LVE) approach that integrates character values with the principles of religious moderationtn the Madania educational environment. This study uses a type of qualitative research method with a case study approach. The findings indicate that Madania School adopts the Living Values Education (LVE) approach by integrating an understanding of religious moderation to create an inclusive, multicultural learning environment that focuses on character development. This approach engages educators as role models in applying character values and encourages students to internalize these values through various daily activities and interactions.